Opioid-Free Anesthesia in the Perioperative Setting—A Preliminary Retrospective Matched Cohort Study. Issue 3 (28th December 2020) - Bell, Austin; Andrews, Christopher; Highland, Krista B; Senese Forbes, Angela
ABSTRACT: Introduction: Anesthesiologists have long used multimodal analgesia for effective pain control. Opioid-sparing anesthetics are gaining popularity among practitioners in light of increasing concerns for both immediate opioid side effects and the long-term opioid misuse among susceptible patients. Currently, there is a critical gap in knowledge regarding outcomes after an opioid-free anesthetic (OFA) during general anesthesia. We hypothesized that an opioid-free general anesthetic will not be inferior to a traditional opioid anesthetic (OA) as measured by the perioperative outcomes of postanesthesia care unit (PACU) duration, 12-hour postoperative summed pain intensity (SPI12 ) scores, total morphine equivalent doses (MEDs) utilized in the 12-hour postoperative inpatient (MED12 ) and total MEDs utilized in the 90-day outpatient periods (MED90 ). Materials and Methods: Patients were included if they were ≥18 years old, met criteria for American Society of Anesthesiologists classification I-IV, received general endotracheal anesthesia from a single anesthesia provider for a surgical operation in 2016, did not receive intraoperative administration of opioids, and were recovered in the PACU. A total of 25 patients were included in the OFA group and 29 control patients in the OA group ( n = 54). A retrospective chart review of intraoperative records, perioperative pain scores, and medication utilization (inpatient and outpatient) was performed to obtain the data for the analysis of the primary outcomes. Results: In both OFA and OA groups, the continuous outcomes were not normally distributed. Subsequent bivariate tests of the indicated OA versus OFA age ( d = 0.58), surgery duration ( d = 0.24), and preoperative pain score ( d = 0.51) warranted inclusion in the multinomial regression. Surgical duration was not significantly associated with the primary outcomes. However, the continuous variables of age and preoperative Defense and Veterans Pain Rating Scale score were associated with differences in primary outcomes. Every 1-year increase in the age was associated with a 5.06 increase in SPI12 and 5.73 mg increase in MED12 . Every 1-point increase in the preoperative Defense and Veterans Pain Rating Scale score was associated with an 8.45 minutes increase in PACU duration, 11.25 increase in SPI12, 17.85 mg increase in MED12, and 20.83 mg increase in MED90 . In regard to the primary outcomes, there was a lack of significant differences between the OFA and OA groups in all outcomes (PACU duration, mean SPI12, MED12, and MED90 ). Conclusions: To our knowledge, this is the first matched cohort study directly comparing an OFA with a traditional anesthetic for general anesthesia in a wide range of surgical and clinical scenarios. There was no significant difference in SPI12 between the OFA group and OA group, suggesting that patients' subjective pain was similar immediately after surgery whether or not they received intraoperative opioids. Concurrently, no "catch-up" effect was observed as the PACU duration; MED12 and MED90 were not different between the OFA and OA groups. However, there were many covariates identified in this study because of the small sample size or each group. Additional research is needed to explore if these findings can be extrapolated to a larger more heterogeneous population. Our preliminary work suggests that eliminating patient exposure to opioids in the intraoperative period does not have a deleterious effect on perioperative patient outcomes.